The effect of reconstruction parameters on trabecular bone microstructure assessment using cone beam computed tomography dataset / Aso Muhammad Ali Muhammad - Aso Muhammad, Ali Muhammad (2019)
Cone beam computed tomography (CBCT) system is a broadly used imaging modality in dentistry nowadays. It allows the imaging of high contrast structures of the oral region at a high resolution. The effect of CBCT scan parameters on trabecular bone microstructure (Tb.N), (Tb.Th), (Tb.Sp), and (BV/TV) has been studied, while the effect of CBCT reconstruction parameters is still lacking. Five sectioned maxillae of adult Dorper male sheep (age ranging from 20-48 months and body weight 50-60 kg) were scanned using a CBCT system (Carestream 9000, Kodak) and a Micro-CT (μCT) system (SkyScan 1076, Kontich, Belgium). In the first part of this study, the images for μCT and CBCT were processed and analyzed to study the reliability of CBCT trabecular bone microstructure assessment in comparison with Micro-CT. In the second part of this study, the effect of CBCT reconstruction parameters (reconstruction voxel size, threshold value, and the size and content of the region of interest) on trabecular bone microstructure assessment were evaluated. The statistical analysis showed that CBCT is reliable for the trabecular microstructure measurement in comparison with μCT. For the reconstruction voxel size, there was no significant difference between different reconstruction voxel sizes (76, 100, and 200 μm3 ). For the threshold value, an increase and decrease in the chosen optimal value by 15% was done. Decreasing the chosen optimal value (by 15%) showed significant difference on all trabecular bone parameters, whereas increasing the value had no significant effect. Lastly, the region of interest (Group 1, ROI that only contained trabecular bone, Group 2, ROI contained cortical bone and trabecular bone) showed the inclusion of cortical bone in the ROI showed significant difference on the Tb.Th and BV/TV measurements. In conclusion, BONE MICROSTRUCTURE ASSESSMENT USING CONE BEAM COMPUTED TOMOGRAPHY DATASET iv CBCT (Carestream 9000, Kodak) is reliable for the trabecular bone microstructure assessment. However, the selected CBCT reconstruction parameters can compromise the trabecular bone microstructure measurement